Slide top coffee table / Ahmad Faris Ikhwan Abdullah - Abdullah, Ahmad Faris Ikhwan (2022)
Furniture plays an important role in explaining the way of life of an individual and also known as a manageable object that can support human activities. Coffee table is one type of furniture that can be used to put things on it and will be placed at a living hall. But, limitation of space will restrict users in buying furniture. There is a need to design a furniture with dual function characteristic to overcome this problem. In this study, a product with dual function characteristic (as a coffee table and storage box) is designed and manufactured using Pinus radiata. Sliding table top is applied to give innovation to this product. Then, online survey is conducted to 150 respondents from different demographic factors in determining the acceptance of correspondents on the properties of this product. The results show that there is no significant difference based on gender, age, profession and income. Most of the respondents satisfied with the properties of this product especially female respondents. It can be concluded that this product has potential to be commercialized in furniture market.